Emerging Trends on Brazilian Connected Students Behavior - Passarelli, Brasilina; Angeluci, Alan César Belo (Páginas a&b: arquivos e bibliotecas, 2020)
This paper aims to present emerging trends of Brazilian connected students towards the use and appropriation of ICT resources through data of two national surveys: 2014 #Connected Youth Brazil and 2018 ICT in Education Survey. #Connected Youth Brazil was developed by the School of the Future Research and Culture Laboratory at the University of São Paulo, NACE EF-USP (www.futuro.usp.br), in association with Telefonica Vivo Foundation Brazil (http://fundacaotelefonicavivo.org.br). The survey interviewed 1,440 Brazilian youngster and also developed focus groups sessions with celebrities and educators plus navigation observation through a special software applied to ten authorized adolescents. 2018 ICT in Education survey was developed by Brazilian Internet Steering Committee and interviewed 11,361 students plus teachers and directors. Main findings are: smartphones to democratize Internet connection; students challenged by fake news and information sources; schools are not the main place of connection and students are autonomous learners regarding media literacy. Keywords: Brazilian connected students behavior; #Connected Youth Brazil Survey; Media and Information Literacy (MIL) - Brazil; 2018 ICT in Education CGI Survey.